2014
DOI: 10.1111/echo.12545
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Echocardiographic Epicardial Fat Thickness with Severity of Coronary Artery Disease in Patients with Acute Myocardial Infarction

Abstract: The aim of this study was to test the hypotheses that epicardial adipose tissue (EAT) can be a marker of severe coronary artery disease in patients with acute myocardial infarction. Overall, 373 cases who underwent coronary angiography were classified into 2 groups by SYNTAX score: low-score and high-score group. EAT was measured by transthoracic echocardiography. Obtained data were compared using Pearson correlation analyses and univariate and multiple logistic regression analysis. The results showed that EAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 15 publications
(28 reference statements)
4
39
0
1
Order By: Relevance
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[38][39][40][41][42][43][44][45] Table 1 presents a summary of the included manuscripts. All systematized manuscripts contain a concise and clear portrayal of the inclusion and exclusion criteria and the method for assessing EAT, either through cardiac CT or TTE (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…42 Most researchers (n = 6) used the Receiver Operator Characteristics (ROC) curve and the area under the curve for the determination of the cut-off value for EAT values that predicted the study outcome. [37][38][39][40][41]45 All selected articles used Spearman or Pearson correlation coefficient statistics for evaluating the link between epicardial fat and other clinical and laboratory variables.…”
Section: Statistical Analysis and Study Design Of The Selected Manuscmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang T. et al (32) suggested that EFT could serve as a marker of severe CAD in patients with acute myocardial infarction (AMI). This study highlights the correlation between echocardiographic EFT and the severity of CAD.…”
Section: Discussionmentioning
confidence: 99%